SOFL Three-Step Approach to Construct the Formal Specification of a Brain Tumor Treatment System - A Rahman, Mat; Cheah, Wai Shiang; Liu, Shaoying (Universiti Malaysia Sarawak, 2013)
The SOFL three-step approach to the construction of formal specifications has been proposed and applied in information systems, but its effectiveness and applicability have not yet been demonstrated in developing safety critical systems. In this paper, we describe an application of the SOFL approach to the construction of a formal specification for the brain tumor treatment system. This case study demonstrates the suitability of SOFL for safety-critical system developments and provides us with an insight into the knowledge of how the SOFL three-step specification approach can be effectively supported.